Effects of Arbuscular Mycorrhization in Sterile and Non-sterile Soils - Abdulla Saleh Al-Khaliel (Tropical Life Sciences Research, 2010)
Mycorrhiza, a mutualistic association between fungi and higher plants, has been documented extensively, but much less is known about the development of arbuscular mycorrhizal (AM) fungi and their effects on the growth of peanuts (Arachis hypogea L.). Therefore, the mycorrhizal status of Glomus spp. was investigated in the following diverse substrate soil conditions: non-autoclaved soil, autoclaved soil and autoclaved soil plus soil microbiota. The results indicated that both the arbuscular mycorrhizae, Glomus mosseae (Nicol. & Gerd.) Gerd. & Trappe, and Glomus fasciculatum (Thaxter) Gerd. & Trappe emend. Walker & Koske were infective to peanut, but displayed a differential impact on peanut growth depending on the microbial biomass content of the substrate soils. G. mosseae proved to be the most effective at improving peanut growth. Mycorrhiza, satu perhubungan mutualistik antara fungi dan tumbuhan peringkat tinggi, telah didokumentasikan secara terperinci, tetapi fakta-fakta tentang perkembangan fungi arbuscular mycorrhizal dan kesan-kesannya terhadap pertumbuhan kacang tanah (Arachis hypogea L.) kurang diketahui. Maka, status mycorrhizal Glomus spp. telah dikaji di dalam pelbagai keadaan/jenis tanah: tanah yang tidak diautoklav, tanah yang diautoklav dan tanah yang diautoklav bersama mikrobiota. Keputusan menunjukkan bahawa keduadua arbuscular mycorrhizal (AM) Glomus mosseae (Nicol. & Gerd.) Gerd. & Trappe, and Glomus. fasciculatum (Thaxter) Gerd. & Trappe emend. Walker & Koske menjangkiti kacang tanah, tetapi telah memberi impak yang berbeza terhadap pertumbuhan kacang tanah, bergantung kepada kandungan biomas mikrob tanah. G. mosseae didapati yang paling efektif dalam memperbaiki pertumbuhan kacang tanah.